Description of larva and pupa of Phylloicus abdominalis Ulmer, 1905 (Trichoptera: Calamoceratidae) - Huamantinco, A. A.; Dumas, L. L.; Nessimian, J. L. (Zootaxa, 2005)
The larva and pupa of Phylloicus abdominalis Ulmer, 1905 from a tributary of the Rio Preto, Itatiaia, State of Rio de Janeiro, Brazil, are described, illustrated and compared to other Neotropical species in the genus.